Complete nucleotide sequence, genomic organization and phylogenetic analysis of Citrus leprosis virus cytoplasmic type - Locali-Fabris, E. C.; Freitas-Astua, J.; Souza, A. A.; Takita, M. A.; Astua-Monge, G.; Antonioli-Luizon, R.; Rodrigues, V; Targon, M. L. P. N.; Machado, M. A. (Soc General Microbiology, 2006)
The complete nucleotide sequence of the genomic RNA 1 (8745 nt) and RNA 2 (4986 nt) of Citrus leprosis virus cytoplasmic type (CiLV-C) was determined using cloned cDNA. RNA 1 contains two open reading frames (ORFs), which correspond to 286 and 29 kDa proteins. The 286 kDa protein is a polyprotein putatively involved in virus replication, which contains four conserved domains: methyltransferase, protease, helicase and polymerase. RNA 2 contains four ORFs corresponding to 15, 61, 32 and 24 kDa proteins, respectively. The 32 kDa protein is apparently involved in cell-to-cell movement of the virus, but none of the other putative proteins exhibit any conserved domain. The 5' regions of the two genomic RNAs contain a 'cap' structure and poly(A) tails were identified in the 3'-terminals. Sequence analyses and searches for structural and non-structural protein similarities revealed conserved domains with members of the genera Furovirus, Bromovirus, Tobravirus and Tobamovirus, although phylogenetic analyses strongly suggest that CiLV-C is a member of a distinct, novel virus genus and family, and definitely demonstrate that it does not belong to the family Rhabdoviridae, as previously proposed. Based on these results it was proposed that Citrus leprosis virus be considered as the type member of a new genus of viruses, Cilevirus.